Species delimitation in the Andean grasshopper genus Orotettix Ronderos & Carbonell (Orthoptera: Melanoplinae): an integrative approach combining morphological, molecular and biogeographical data - Pocco, Martina Eugenia (2015)
The reciprocal illumination nature of integrative taxonomy through hypothesis testing, corroboration and revision is a powerful tool for species delimitation as more than one source has to support the hypothesis of a new species. In this study, we applied an integrative taxonomy approach combining molecular and morphological data sets with distributional patterns to examine the level of differentiation between and within the grasshopper Orotettix species. Orotettix was described based on five valid species distributed in the Andes of Peru. In our study, initially a molecular-based hypothesis was postulated and tested against morphological data and geographical patterns of distribution. Results from molecular and morphological analyses showed agreement among the species delimitation in Orotettix, and were also consistent with the geographical distribution. The analyses allowed us to delimit five new species for the genus (O. lunatus sp. nov., O.astreptos sp. nov., O. colcaensis sp. nov., O.paucartambensis sp. nov. and O.dichrous sp. nov.) from the Eastern and Western Cordilleras of Peru. We also provide critical knowledge on the phylogenetic relationships and distribution of the genus and conduct a revision of Orotettix.